Back Cover: Theranostics for MRI‐guided therapy: Recent developments (View 3/2022). Issue 3 (30th May 2022) - Zhang, Ziwei; Zhou, Feng‐Lei; Davies, Gemma‐Louise; Williams, Gareth R.
Abstract : In article number 20200134, Gareth Williams and coworkers have presented magnetic resonance imaging is a powerful method for imaging in vivo and hence for medical diagnosis. It can also be combined with anti‐cancer therapeutic agents to generate theranostics for simultaneous imaging and therapy.